Implementation of the MASK-Air® App for Rhinitis and Asthma in Older Adults: MASK@Puglia Pilot Study - Ventura, Maria Teresa; Giuliano, Antonio Francesco Maria; Buquicchio, Rosalba; Bedbrook, Anna; Czarlewski, Wienczyslawa; Laune, Daniel; Patella, Vincenzo; Canonica, Giorgio Walter; Bousquet, Jean (International archives of allergy and immunology, 2022)
MASK-air® is an app whose aim is to reduce the global burden of allergic rhinitis and asthma. A transfer of innovative practices was performed to disseminate and implement MASK-air® in European regions. The aim of the study was to examine the implementation of the MASK-air® app in older adults of the Puglia TWINNING in order to investigate (i) the rate of acceptance in this population, (ii) the reasons for refusal and (iii) the evaluation of the app after its use. All consecutive geriatric patients aged between 65 and 90 years were included by the outpatient clinic of the Bari Geriatric Immunoallergology Unit. After a 1-h training session, older adults used the app for 6 months. A 6-item questionnaire was developed by our unit to evaluate the impact of the app on the management of the disease and its treatment. Among the 174 recruited patients, 102 accepted to use the app (mean age, SD: 72.4 ± 4.6 years), 6 were lost to follow-up, and 63 had a low education level. The reasons given not to use the app included lack of interest (11%), lack of access to a smartphone or tablet (53%), low computer literacy (28%), and distrust (8%). At follow-up, the overall satisfaction was high (89%), the patient considered MASK-air® "advantageous" (95%), compliance to treatment was improved (81%), and the rate of loss to follow-up had decreased to 6%. Older adults with a low level of education can use the MASK-air® app after a short training session.